Arellano, Ignacio (ed.), Poesía clandestina y de protesta política del Siglo de Oro, Madrid, Cátedra, 2025, 424p. ISBN: 978-84-376-4912-2. 17,95€ - Jesús-M. Usunáriz (Memoria y Civilización)
Book Review